PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN CORPORATE GOVERNANCE (CG) TERHADAP AGRESIVITAS PAJAK - Putri Rohmatul Ummah; Erma Setiawati (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Tax aggressiveness is a step taken by the company as a strategy to minimize the tax burden that should be paid by the company. In this study, the tax aggressiveness variable uses a proxy for the ETR value. The low value of a company's ETR illustrates that the tax aggressiveness of the company is getting higher. This study aims to determine the effect of Corporate Social Responsibility and Corporate Governance on Tax Aggressiveness using the ETR proxy. The population in this study are manufacturing companies listed on the IDX in 2018-2020. The companies that were selected as the sample after deducting several criteria were 182 company data. The results of the study provide evidence of the influence of Corporate Social Responsibility on ETR as a proxy for tax aggressiveness. Companies with a higher level of Corporate Social Responsibility , the value of ETR increases, which illustrates the lower level of tax aggressiveness carried out by the company. Keywords: Tax Aggressiveness, Corporate Social Responsibility, Corporate Governance